Load carrying capability of liquid filled cylindrical shell structures under axial compression - Hussain Shah, Qasim; Mujahid, Mohammad; Al-Atabi, Mushtak; Abakrb, Yousif A. (Taylor's University, 2011)
Empty and water filled cylindrical Tin (Sn) coated steel cans were loaded under axial compression at varying loading rates to study their resistance to withstand accidental loads. Compared to empty cans the water filled cans exhibit greater resistance to axially applied compression loads before a complete collapse. The time and load or stroke and load plots showed three significant load peaks related to three stages during loading until the cylinder collapse. First peak corresponds to the initial structural buckling of can. Second peak occurs when cylindrical can walls gradually come into full contact with water. The third peak shows the maximum load carrying capability of the structure where pressurized water deforms the can walls into curved shape until can walls fail under peak pressure. The collapse process of water filled cylindrical shell was further studied using Smooth Particle Hydrodynamics (SPH) technique in LSDYNA. Load peaks observed in the experimental work were successfully simulated which substantiated the experimental work.